Laminate

JP7631716B2Active Publication Date: 2025-02-19TORAY INDUSTRIES INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020161690
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-19
Filing Date
2020-09-28
Publication Date
2025-02-19
Estimated Expiration
2040-09-28

AI Technical Summary

Benefits of technology

【0018】 本発明によれば、伸縮性を持ちながら、後加工適性に優れる積層体を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631716000022
    Figure 0007631716000022
  • Figure 0007631716000023
    Figure 0007631716000023
  • Figure 0007631716000024
    Figure 0007631716000024
Patent Text Reader

Abstract

To provide a laminate having excellent post-processability while having elasticity.SOLUTION: A laminate has a surface layer 1 on at least one side of a resin layer 2. The surface layer 1 has a storage elastic modulus of 1,000 MPa or more at 25°C, the laminate has a haze of 10% or less, and the laminate has a recovery rate of 50% or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate that combines stretchability and suitability for post-processing. [Background technology]

[0002] In recent years, display-mounted devices, such as smartphones, tablets, personal computers, and LCD TVs, and various other devices have become widespread, and many film and sheet materials made of synthetic resins are used as their components. In this context, research and development of flexible and wearable devices has been actively carried out in recent years, and development of deformable devices and components is progressing.

[0003] Due to this situation, new technical fields are likely to emerge that will be difficult to apply using the materials that have been used in conventional displays and devices, and the need for new materials with high flexibility and stretchability is expected to increase.

[0004] On the other hand, as an example of an existing material having flexibility and stretchability, Patent Document 1 proposes "a laminate having at least a layer made of a first polyethylene, a thermoplastic polyurethane layer laminated on the layer made of the first polyethylene, and a layer made of a second polyethylene laminated on the thermoplastic polyurethane layer, wherein the heat of crystallization of the first polyethylene is greater than the heat of crystallization of the second polyethylene."

[0005] Furthermore, Non-Patent Document 1 lists so-called "silicone materials" and proposes a sheet material using silicone rubber as an example of the silicone material.

[0006] Furthermore, Patent Document 2 proposes "an elastic film comprising an SBS resin composition prepared by mixing a styrene-butadiene-styrene copolymer (SBS-A) containing 65 to 95% by mass of a styrene component and a styrene-butadiene-styrene copolymer (SBS-B) containing 5 to 40% by mass of a styrene component in a composition ratio of (SBS-A) / (SBS-B) = 75 / 25 to 95 / 5, and a filler (C) blended in an amount of 20 to 45 parts by mass per 100 parts by mass of the SBS resin composition, and having a specific gravity of 1.10 to 1.32."

[0007] Furthermore, Patent Document 3 proposes "a foamed urethane sheet comprising a substrate which is any one of a polyethylene terephthalate film, a polypropylene film, and a methylpentene polymer film and has an adhesive on one side, and a foam obtained by heating the substrate, wherein the organic solvent is a mixed solution of toluene and methyl ethyl ketone, and the foam is composed of fine cells with a continuous air permeability structure."

[0008] Furthermore, if one is simply looking for a material that has high flexibility, one example is the adhesive material described in Non-Patent Document 2, although it cannot be said to be a material that has elasticity. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2013-91223 A [Patent Document 2] JP 2008-88293 A [Patent Document 3] JP 2014-231170 A [Non-patent literature]

[0010] [Non-Patent Document 1] Silicone Handbook, Nikkan Kogyo Shimbun, 1990 [Non-Patent Document 2] Learn about adhesives from the basics - Why does it stick? Why does it peel off? - Maruzen Publishing Co., Ltd. Summary of the Invention [Problem to be solved by the invention]

[0011] However, when the inventors checked the material proposed in Patent Document 1, they found that although it had a certain degree of stretchability, it lacked heat resistance at high temperatures and was unsuitable for post-processing involving heating, which is necessary for application as a component of displays and devices. In addition, the material was unsuitable for post-processing involving coating, and had poor adhesion to different materials.

[0012] In addition, the silicone rubber material proposed in Non-Patent Document 1 had a certain degree of elasticity and tack-prevention properties, but had poor adhesion to different materials and was not suitable for post-processing. In addition, the elasticity was also insufficient.

[0013] Next, with regard to the material proposed in Patent Document 2, although a certain degree of flexibility was confirmed, it was found that the stretchability and transparency were insufficient.

[0014] Furthermore, although the material proposed in Patent Document 3 was confirmed to have a certain degree of flexibility and stretchability, it had insufficient transparency.In addition, due to the presence of foamed portions, it was found to be unsuitable for post-processing steps involving coating.

[0015] In addition, the material proposed in Non-Patent Document 2 was confirmed to have a certain degree of flexibility, but was not a material that exhibited stretchability. In addition, since it was an adhesive material, it was not suitable for post-processing and did not exhibit tack prevention properties.

[0016] Therefore, an object of the present invention is to provide a laminate that has stretchability and excellent post-processability. [Means for solving the problem]

[0017] In order to solve the above problems, the present inventors have conducted extensive research and have completed the following invention. <1> A laminate having a surface layer on at least one surface of a resin layer, The storage modulus of the surface layer at 25°C is 1,000 MPa or more, The haze of the laminate is 10% or less, A laminate, characterized in that the laminate has a recovery rate of 50% or more. Effect of the Invention

[0018] According to the present invention, it is possible to obtain a laminate having excellent stretchability and excellent suitability for post-processing. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 is a cross-sectional view showing an example of a laminate according to the present invention. [Diagram 2] FIG. 1 is a cross-sectional view showing an example of a laminate according to the present invention. [Diagram 3] FIG. 1 is a cross-sectional view showing an example of a laminate according to the present invention. [Figure 4] 1 is a cross-sectional view showing an example of a method for forming a laminate in the present invention. [Diagram 5] 1 is a cross-sectional view showing an example of a method for forming a laminate in the present invention. [Figure 6] 1 is a cross-sectional view showing an example of a method for forming a laminate in the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Before describing the embodiments of the present invention, the problem with the conventional technology, that is, the compatibility between stretchability and suitability for post-processing, will be considered from the viewpoint of the present inventor.

[0021] [Comparison of the present invention and the prior art] In the prior art, there are materials that exhibit elasticity, but because of their elasticity, they lack tack prevention and reworkability. Therefore, even if a material is suitable from the viewpoint of elasticity, it is difficult to process it well and to actually apply it in applications such as displays, devices, sensors, etc., because film materials are often used after various post-processing processes. In addition, in applications where such elastic materials come into direct contact with human skin, such as wearable sensors and sanitary materials, the elasticity of the materials makes them tacky, which can cause discomfort when they come into contact with human skin, and they may not be able to be peeled off properly when correcting the attachment position, resulting in insufficient reworkability.

[0022] In addition, materials that exhibit elasticity swell when they absorb a solvent, making them unsuitable for post-processing involving coating. On the other hand, silicone rubber materials are an example of materials that exhibit elasticity but absorb relatively little solvent, but silicone rubber materials tend to repel the coating liquid during the coating process, making post-processing difficult, and even if they could be coated, they have poor adhesion to other materials, making them unsuitable for post-processing.

[0023] Therefore, the present inventors have investigated a method of imparting the above-mentioned tack prevention and reworkability to such a material exhibiting elasticity while making use of its characteristics. As such a method, a method of imparting a specific shape to the elastic surface and a method of roughening the surface were also effective. However, since the surface shape is no longer smooth and the resin layer is whitened due to light scattering caused by the surface shape, it may be unsuitable for some printing processes and applications requiring transparency. Therefore, the present inventors have searched for a method other than the above and found that it is effective to form a surface layer having a certain hardness or more on the elastic layer. At this time, it was found that by having the surface layer have sufficient adhesion to the resin layer, the elasticity of the resin layer can be expressed as a laminate of the resin layer and the surface layer without impairing the inherent elasticity of the resin layer, and good transparency can be achieved at the same time. Furthermore, when the present inventors have examined the above surface layer in detail, they have found that there is a preferred range for the hardness of the surface layer. As described above, the elastic material can improve its suitability for post-processing by having a surface layer, but it was found that this effect requires the surface layer to have a certain hardness or more.

[0024] Specifically, it is preferable that the laminate has a surface layer on at least one side of a resin layer, the surface layer has a storage modulus of 1,000 MPa or more, and the haze of the laminate is 10% or less. It is also preferable that the recovery rate of the laminate is 50% or more.

[0025] Furthermore, the present inventors have examined the configuration of the laminate and found that the stretchability of the laminate can be improved by setting the hardness of the resin layer at a certain level or less.

[0026] Specifically, it is preferable that the storage modulus of the resin layer at 25° C. is 100 MPa or less, and the 5% strain stress of the resin layer is 300 MPa or less.

[0027] Furthermore, in examining the laminate, the inventors also verified the type of resin constituting the resin layer. Examples of materials that exhibit elasticity include thermoplastic resins and crosslinkable resins, and examples of such thermoplastic resins include thermoplastic urethane and olefin-based elastomers. However, having thermoplasticity means that it is prone to plastic deformation. That is, plastic deformation is a property derived from the polymer structure that constitutes the resin, and a characteristic of thermoplasticity is that large plastic deformation occurs when heated, but heating only promotes plastic deformation, and plastic deformation can occur even at room temperature or in a low temperature environment. In particular, in a situation where distortion is continuously applied from the outside for a long time or a situation where large deformation is applied, plastic deformation occurs even in a situation without heating. If plastic deformation occurs, it means that the resin layer does not return to its original shape even if the stress is released after deformation, resulting in impaired resilience. Therefore, it is considered that thermoplastic resins are unsuitable materials for applications that require high resilience in various environments.

[0028] On the other hand, it has been found that among materials exhibiting elasticity, crosslinkable resins are more preferable in applications requiring high restoring properties in various environments without the above-mentioned problems. Examples of materials exhibiting elasticity include urethane-based elastomers, acrylic-based elastomers, and silicone rubber materials, and the resin constituting the resin layer in the laminate of the present invention is also a crosslinkable resin. As mentioned above, silicone rubber materials were not considered to be a preferable material for another reason, but they can be considered to be a preferable material in terms of exhibiting high restoring properties in various environments.

[0029] Specifically, the resin layer is preferably made of a crosslinkable resin.

[0030] Furthermore, when the present inventors examined the post-processability, they found that it is preferable to form the laminate of the present invention by forming the laminate on a release film and then peeling off the release film. This method improves the handling properties in post-processing because the release film functions as a carrier for the laminate. Furthermore, if the surface of the laminate that contacts the surface layer is a release film, the surface layer can be exposed by peeling off the release film at any time, so that the surface layer can be protected from external loads and the surface layer can be exposed according to the timing of post-processing.

[0031] Specifically, it is preferable that the laminate further comprises a supporting substrate, the supporting substrate being in contact with the surface layer opposite the resin layer, and the laminate consisting of the resin layer and the surface layer being peelable from the supporting substrate.

[0032] [Mode of the present invention] Hereinafter, the embodiment of the present invention will be described in detail.

[0033] A laminate having a surface layer on at least one surface of a resin layer, The storage modulus of the surface layer at 25°C is 1,000 MPa or more, The haze of the laminate is 10% or less, A laminate, characterized in that the laminate has a recovery rate of 50% or more.

[0034] The methods for measuring the storage modulus, haze, and recovery rate will be described later.

[0035] In the laminate of the present invention, the surface layer preferably has a storage modulus of 1,000 MPa or more, and more preferably 1,500 MPa or more.

[0036] Regarding the storage modulus of the surface layer at 25°C, if the 5% strain stress of the storage modulus is 1,000 MPa or more, it exhibits good tack prevention properties and improves suitability for post-processing. The higher the 5% strain stress, the better the tack prevention properties, but the upper limit for resin materials is thought to be about 10,000 MPa. On the other hand, if the storage modulus is less than 1,000 MPa, the tack prevention properties may be insufficient and the suitability for post-processing may be insufficient.

[0037] From the viewpoint of transparency, the haze of the laminate of the present invention is preferably 10% or less, and more preferably 5% or less.

[0038] Regarding the haze of the laminate, when the haze is 10% or less, the laminate exhibits good transparency. The lower the haze, the higher the transparency, but the lower limit of the haze is 0%. On the other hand, when the haze exceeds 10%, the laminate may be unsuitable for applications requiring transparency.

[0039] From the viewpoint of stretchability, the restoration rate of the laminate is preferably 50% or more, more preferably 70% or more, and particularly preferably 80% or more.

[0040] Regarding the restoration rate of the laminate, if the restoration rate is 50% or more, even if the laminate is deformed by applying a load, the effect of returning to the original shape when the load is removed is large, so it is preferable. The higher the restoration rate, the greater the above effect, but the upper limit of the restoration rate is 100%.

[0041] Furthermore, from the viewpoint of stretchability, it is preferable that the laminate satisfies the following condition 2.

[0042] Condition 1: The storage modulus of the resin layer at 25°C is 100 MPa or less.

[0043] From the viewpoint of stretchability, in the laminate of the present invention, the storage modulus of the resin layer at 25° C. is preferably 100 MPa or less, more preferably 50 MPa or less.

[0044] Regarding the storage modulus of the resin layer at 25°C, if the storage modulus is 100 MPa or less, the laminate exhibits good elasticity. There is no particular limit to the lower limit of the storage modulus, and the lower the storage modulus, the better the elasticity, but if it is extremely low, the rigidity of the laminate may be insufficient, so the lower limit is considered to be about 0.01 MPa. On the other hand, if the storage modulus exceeds 100 MPa, the elasticity of the laminate may be insufficient depending on the application.

[0045] The storage modulus of the resin layer can be set to 100 MPa or less, for example, by using a material described later.

[0046] Furthermore, from the viewpoint of stretchability, it is preferable that the laminate satisfies the following condition 2.

[0047] Condition 2: The 5% strain stress of the resin layer is 100 MPa or less.

[0048] From the viewpoint of stretchability, in the laminate of the present invention, the 5% strain stress of the resin layer is preferably 100 MPa or less, and more preferably 50 MPa or less.

[0049] Regarding the 5% strain stress of the resin layer, if the 5% strain stress is 100 MPa or less, the laminate exhibits good elasticity. There is no particular limit to the lower limit of the 5% strain stress, and the lower the stress, the better the elasticity. However, if the stress is extremely low, the rigidity of the laminate may be insufficient, so the lower limit is considered to be about 0.01 MPa. On the other hand, if the 5% strain stress exceeds 100 MPa, the elasticity of the laminate may be insufficient depending on the application.

[0050] The 5% strain stress of the resin layer can be set to 100 MPa or less, for example, by using the materials described below.

[0051] Furthermore, from the viewpoint of restorability, it is preferable that the laminate satisfy the following condition 3.

[0052] Condition 3: The resin layer is made of a crosslinkable resin.

[0053] The resin layer of the present invention is preferably made of a crosslinkable resin, which has the above-mentioned effect of providing high restorability in various environments.

[0054] Furthermore, from the viewpoint of post-processability, the laminate further includes a supporting substrate, A supporting substrate is in contact with the surface of the surface layer opposite to the resin layer, It is preferable that the laminate consisting of the resin layer and the surface layer is peelable from the supporting substrate.

[0055] In the laminate of the present invention, the above-mentioned laminate structure is preferred from the viewpoints of adhesion between the resin layer and the surface layer, suppression of haze in the laminate, and improvement of the quality. It is also preferred because, when post-processing is performed on the surface layer, the surface layer can be exposed by peeling off the release film at any time.

[0056] Furthermore, in the method for producing the laminate, The method includes a step of applying a coating composition containing components constituting a surface layer to one surface of a supporting substrate, Furthermore, a coating composition containing components constituting a resin layer is applied to the surface of the surface layer opposite to the supporting substrate. The method for producing a laminate is preferably characterized by including a coating step.

[0057] [Release film] The release film used in the present invention may be a base film made of a resin having releasability by itself, or a base film having releasability imparted thereto by forming a release layer on the surface of the base film. The material for forming the release layer may be a commercially available general-purpose resin having releasability or a general-purpose release coating material.

[0058] The resin constituting the substrate film used in the release film of the present invention may be any of a thermoplastic resin and a thermosetting resin, and may be a homogeneous resin, a copolymer, or a blend of two or more kinds. The resin constituting the supporting substrate is preferably one having good moldability, and from that point of view, a thermoplastic resin is more preferable.

[0059] Examples of thermoplastic resins include polyolefin resins such as polyethylene, polypropylene, polystyrene, and polymethylpentene, alicyclic polyolefin resins, polyamide resins such as nylon 6 and nylon 66, aramid resins, polyimide resins, polyester resins, polycarbonate resins, polyarylate resins, polyacetal resins, polyphenylene sulfide resins, fluororesins such as tetrafluoroethylene resin, trifluoroethylene resin, trifluorochloroethylene resin, tetrafluoroethylene-hexafluoropropylene copolymer, and vinylidene fluoride resin, acrylic resins, methacrylic resins, polyacetal resins, polyglycolic acid resins, and polylactic acid resins. Examples of thermosetting resins include phenolic resins, epoxy resins, urea resins, melamine resins, unsaturated polyester resins, polyurethane resins, polyimide resins, and silicone resins. The thermoplastic resin is preferably a resin with sufficient stretchability and conformability. From the viewpoint of moldability for forming a concave-convex structure on the surface, the thermoplastic resin is more preferably a polyester resin, a polyolefin resin, a polycarbonate resin, an acrylic resin, or a methacrylic resin. In particular, as a resin that has releasability by itself, a polyolefin resin is particularly preferable.

[0060] The polyester resin in the present invention is a general term for a polymer having an ester bond as the main bond in the main chain, and is obtained by polycondensation of an acid component and its ester with a diol component. Specific examples include polyethylene terephthalate, polypropylene terephthalate, polyethylene-2,6-naphthalate, and polybutylene terephthalate. These may also be copolymerized with other dicarboxylic acids and their esters or diol components as the acid component or diol component. Among these, polyethylene terephthalate and polyethylene-2,6-naphthalate are particularly preferred in terms of transparency, dimensional stability, heat resistance, and the like.

[0061] The substrate film may contain various additives, such as an antioxidant, an antistatic agent, a crystal nucleating agent, inorganic particles, organic particles, a viscosity reducer, a heat stabilizer, a lubricant, an infrared absorbing agent, an ultraviolet absorbing agent, a dopant for adjusting the refractive index, etc. The supporting substrate may have either a single layer structure or a laminate structure.

[0062] The surface of the substrate film may be subjected to various surface treatments before forming the laminate. Examples of the surface treatments include chemical treatment, mechanical treatment, corona discharge treatment, flame treatment, ultraviolet irradiation treatment, high frequency treatment, glow discharge treatment, active plasma treatment, laser treatment, mixed acid treatment, and ozone oxidation treatment. Among these, glow discharge treatment, ultraviolet irradiation treatment, corona discharge treatment, and flame treatment are preferred, and glow discharge treatment and ultraviolet treatment are more preferred.

[0063] In addition, it is also possible to provide a functional layer such as an easy-adhesion layer, an antistatic layer, an undercoat layer, an ultraviolet absorbing layer, or a release layer on the surface of the base film in advance, separate from the laminate of the present invention. In the laminate of the present invention, it is particularly preferable to provide a release layer in order to reduce the peel force between the base film and the laminate.

[0064] Examples of films made of polyester resin provided with the above-mentioned release layer include "Therapeel" (registered trademark) manufactured by Toray Film Processing Co., Ltd., "Unipeel" (registered trademark) manufactured by Unitika Ltd., "Panapeel" (registered trademark) manufactured by Panac Corporation, "Toyobo Ester" (registered trademark) manufactured by Toyobo Co., Ltd., and "Purex" (registered trademark) manufactured by Teijin Limited, and these products can be used.

[0065] [Laminate] The laminate of the present invention may be in a planar state or in a three-dimensional shape after molding, so long as it has the above-mentioned physical properties. The number of layers of the laminate is not particularly limited as long as it has two or more layers, and may be formed of two layers or three or more layers.

[0066] The thickness of the laminate is not particularly limited, but the lower limit is preferably 1 μm or more, more preferably 5 μm or more, and even more preferably 10 μm or more. The upper limit is preferably 500 μm or less, more preferably 300 μm or less, and particularly preferably 200 μm or less. The thickness of the laminate can be selected depending on the other functions described above.

[0067] The laminate may have other functions such as gloss, fingerprint resistance, moldability, designability, scratch resistance, stain resistance, solvent resistance, antireflection, antistatic, electrical conductivity, heat ray reflection, near infrared absorption, electromagnetic wave shielding, and easy adhesion, in addition to the elasticity and tackiness that are the object of the present invention.

[0068] Furthermore, one or more layers may be further formed on the laminate, for example, a functional layer having the above-mentioned functions, an adhesive layer, an electronic circuit layer, a printing layer, an optical adjustment layer, or other functional layers may be provided.

[0069] [Paint composition] The method for producing the laminate of the present invention is not particularly limited, but the laminate of the present invention can be obtained through a process of applying a coating composition containing components constituting a resin layer and a surface layer to the surface of a release film, a process of drying as necessary, and a process of curing the components. Here, the "coating composition" refers to a liquid consisting of a solvent and a solute, and refers to a material that can form a resin layer and a surface layer by applying it to the release film described above, volatilizing and removing the solvent in a drying process, and curing it.

[0070] Here, the "type" of coating composition refers to liquids that have different types of solutes that make up the coating composition, even if only partially. The solutes consist of resins or materials that can form them in the coating process (hereinafter referred to as precursors), particles, and various additives such as polymerization initiators, curing agents, catalysts, leveling agents, UV absorbers, and antioxidants.

[0071] [Paint composition A] In the laminate of the present invention, it is preferable to form a resin layer by using the following coating composition A and applying it onto a release film.

[0072] Coating composition A is a liquid containing components suitable for forming the resin layer of the present invention, and preferably contains a resin or precursor containing the following segments (1) and (2) as a solute. It may also contain a resin or precursor containing the segment (3). (1) A segment including at least one selected from the group consisting of a polycaprolactone segment, a polycarbonate segment, and a polyalkylene glycol segment. (2) Urethane bond (3) At least one of a polysiloxane segment or a polydimethylsiloxane segment.

[0073] The individual segments contained in the components constituting this resin layer can be confirmed by TOF-SIMS, FT-IR, or the like.

[0074] The ratio of the mass parts of the (1), (2), and (3) contained in the coating composition is preferably (1) / (2) / (3)=95 / 5 / 1 to 50 / 50 / 15, and more preferably (1) / (2) / (3)=90 / 10 / 1 to 60 / 40 / 10. Details of (1), (2), and (3) are described below.

[0075] The (1) polycaprolactone segment, polycarbonate segment, and polyalkylene glycol segment will be described in detail later, but the components constituting the resin layer having these segments can improve the elasticity and flexibility of the resin layer. In addition, from the viewpoint of durability of the laminate, it is particularly preferable that the components constituting the resin layer have a polyalkylene glycol segment.

[0076] The details of the urethane bond will be described later, but when the resin constituting the layer A on the surface of the resin layer has this bond, the toughness and stretchability of the laminate can be improved.

[0077] The polysiloxane segment and polydimethylsiloxane segment will be described in detail later, but by including these in the components constituting the resin layer, molecules exhibiting low surface energy can be present at a high density on the outermost surface, thereby improving the solvent resistance of the laminate.

[0078] Another example of a resin that is preferred as a solute for the coating composition is urethane acrylate. Various general-purpose urethane acrylates are available, and it is also possible to synthesize materials with various physical properties depending on the purpose.

[0079] In the present invention, a more preferred embodiment is a method for lowering the glass transition temperature of the resin layer, and one of the means for this is to select the type of urethane acrylate.Similarly, another more preferred embodiment is to use a component obtained by curing a urethane acrylate having a certain number average molecular weight in the resin layer, and one of the means for this is to select the type of urethane acrylate.

[0080] Commercially available examples of urethane acrylates include urethane acrylates manufactured by Asia Kogyo Co., Ltd., urethane acrylates manufactured by Kyoeisha Chemical Co., Ltd., urethane acrylates manufactured by Shin-Nakamura Chemical Co., Ltd., urethane acrylates manufactured by Taisei Fine Chemical Co., Ltd., "New Frontier" (registered trademark) manufactured by Daiichi Kogyo Seiyaku Co., Ltd., "EBECRYL" (registered trademark) manufactured by Daicel-Allnex Corporation, "Shiko" (registered trademark) manufactured by Nippon Gosei Co., Ltd., and urethane acrylates manufactured by DIC Corporation, and these products can be used.

[0081] In addition, it is preferable that the coating composition A contains a resin or precursor containing a polyether segment (4). The resins or precursors containing the segments (1) to (3) may all be present in one type of polymer or oligomer, or may be a mixture of different polymers or oligomers containing each of them.

[0082] In the laminate of the present invention, mechanical properties such as flexibility and elasticity of the resin layer are important. Therefore, a method capable of controlling the structure of the polymer forming the resin layer is preferable. In addition, since the resin layer of the laminate of the present invention is required to have a high level of appearance quality and smoothness of thickness, there is a preferred range for the viscosity of the coating composition A in the manufacturing method of the laminate described below. Furthermore, since the laminate of the present invention is processed in a later step, it is preferable that it is as resistant to solvents as possible.

[0083] Therefore, it is preferable to prepare coating composition A by polymerizing a precursor containing a polyether segment of chemical formula 3, a (meth)acrylic segment of chemical formula 1, and a urethane segment of chemical formula 2 under conditions where the molecular weight can be controlled to prepare an oligomer, and then adding various additives to this to prepare coating composition A, which is then applied to a supporting substrate and crosslinked in the laminate manufacturing method described below to form a resin layer.

[0084] [ka]

[0085] [ka]

[0086] [ka]

[0087] Specifically, it is preferable to polymerize in advance a polyether polyol, a compound containing an isocyanate group, and a hydroxyalkyl (meth)acrylate, or an acrylic-modified polyether polyol and a compound containing an isocyanate group, to produce a urethane acrylate oligomer, to which additives are then added as appropriate to produce a coating composition for forming a laminate.

[0088] Examples of polyether polyols include polyalkylene glycols such as polyethylene glycol, polypropylene glycol, and polytetramethylene glycol, and various derivatives thereof.

[0089] Examples of hydroxyalkyl (meth)acrylates include hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate.

[0090] [Polycaprolactone segment, polycarbonate segment, polyalkylene glycol segment] First, the polycaprolactone segment refers to the segment shown in chemical formula 4. Polycaprolactone includes those in which the repeating unit of caprolactone is 1 (monomer), 2 (dimer), or 3 (trimer), as well as oligomers with up to 35 repeating units of caprolactone.

[0091] [ka]

[0092] Here, n is an integer from 1 to 35.

[0093] The resin containing the polycaprolactone segment preferably has at least one hydroxyl group. The hydroxyl group is preferably located at the terminal of the resin containing the polycaprolactone segment.

[0094] As the resin containing a polycaprolactone segment, polycaprolactone having di- or tri-functional hydroxyl groups is particularly preferred. Specifically, polycaprolactone diol represented by Chemical Formula 5 is

[0095] [ka]

[0096] Here, m+n is an integer between 4 and 35, m and n are integers between 1 and 34, and R is C2H4, C2H4OC2H4, or C(CH3)3(CH2)2. Or a polycaprolactone triol represented by chemical formula 6:

[0097] [ka]

[0098] Here, l+m+n is an integer between 3 and 30, l, m, and n are each an integer between 1 and 28, and R is CH2CHCH2, CH3C(CH2)3, or CH3CH2C(CH2)3. Polycaprolactone polyols such as those shown in Chemical Formula 7, and polycaprolactone-modified hydroxyethyl (meth)acrylate

[0099] [ka]

[0100] Here, n is an integer of 1 to 25, and R can be H or CH3, etc., which is an active energy ray-polymerizable caprolactone. Other examples of active energy ray-polymerizable caprolactone include polycaprolactone-modified hydroxypropyl (meth)acrylate, polycaprolactone-modified hydroxybutyl (meth)acrylate, etc.

[0101] Furthermore, in the present invention, the resin containing a polycaprolactone segment may contain (or be copolymerized with) other segments or monomers in addition to the polycaprolactone segment, for example, a polydimethylsiloxane segment or a polysiloxane segment, or a compound containing an isocyanate compound, which will be described later.

[0102] In the present invention, the weight average molecular weight of the polycaprolactone segment in the resin containing the polycaprolactone segment is preferably 500 to 2,500, and more preferably 1,000 to 1,500. When the weight average molecular weight of the polycaprolactone segment is 500 to 2,500, stretchability and flexibility are further improved, which is preferable.

[0103] Next, the polyalkylene glycol segment refers to a segment shown in chemical formula 8. Polyalkylene glycols include those with two (dimer) or three (trimer) repeating units of alkylene glycol, as well as oligomers with up to 11 repeating units of alkylene glycol.

[0104] [ka]

[0105] n is an integer from 2 to 4, and m is an integer from 2 to 11.

[0106] The resin containing the polyalkylene glycol segment preferably has at least one hydroxyl group. The hydroxyl group is preferably located at the terminal of the resin containing the polyalkylene glycol segment.

[0107] The resin containing the polyalkylene glycol segment is preferably a polyalkylene glycol (meth)acrylate having an acrylate group at the end in order to impart elasticity. The number of acrylate functional groups (or methacrylate functional groups) of the polyalkylene glycol (meth)acrylate is not limited, but it is most preferably monofunctional in terms of the elasticity and flexibility of the cured product.

[0108] Examples of polyalkylene glycol (meth)acrylates contained in the coating composition used to form the laminate include polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, and polybutylene glycol (meth)acrylate, which have structures represented by the following chemical formulas 9, 10, and 11, respectively.

[0109] Polyethylene glycol (meth)acrylate:

[0110] [ka]

[0111] Polypropylene glycol (meth)acrylate:

[0112] [ka]

[0113] Polybutylene glycol (meth)acrylate:

[0114] [ka]

[0115] In chemical formulas 11, 12, and 13, R is hydrogen (H) or a methyl group (-CH3), and m is an integer between 2 and 11.

[0116] In the present invention, it is preferable to react a compound containing an isocyanate group described below with a hydroxyl group of a (poly)alkylene glycol (meth)acrylate to form a urethane (meth)acrylate for use in a laminate, whereby the components constituting the laminate have (2) a urethane bond and (3) a (poly)alkylene glycol segment, and as a result, the toughness of the laminate can be improved as well as the stretchability and flexibility, which is preferable.

[0117] Examples of the hydroxyalkyl (meth)acrylate that is simultaneously blended during the urethane reaction of the compound containing an isocyanate group with the polyalkylene glycol (meth)acrylate include hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate.

[0118] Next, the polycarbonate segment refers to a segment represented by chemical formula 12. Polycarbonates include those having 2 (dimer) or 3 (trimer) carbonate repeat units, as well as oligomers having up to 16 carbonate repeat units.

[0119] [ka]

[0120] n is an integer from 2 to 16. R4 represents an alkylene group or a cycloalkylene group having 1 to 8 carbon atoms.

[0121] The resin containing a polycarbonate segment preferably has at least one hydroxyl group. The hydroxyl group is preferably located at the terminal of the resin containing a polycarbonate segment.

[0122] As the resin containing a polycarbonate segment, a polycarbonate diol having two functional hydroxyl groups is particularly preferable. Specifically, it is represented by Chemical Formula 13. Polycarbonate diol:

[0123] [ka]

[0124] n is an integer of 2 to 16. R represents an alkylene group or cycloalkylene group having 1 to 8 carbon atoms.

[0125] The polycarbonate diol may have any number of repeating carbonate units, but if the number of repeating carbonate units is too large, the strength of the cured product of the urethane (meth)acrylate decreases, so the number of repeating units is preferably 10 or less. The polycarbonate diol may be a mixture of two or more polycarbonate diols having different numbers of repeating carbonate units.

[0126] The polycarbonate diol preferably has a number average molecular weight of 500 to 10,000, more preferably 1,000 to 5,000. If the number average molecular weight is less than 500, it may be difficult to obtain suitable elasticity, and if the number average molecular weight exceeds 10,000, heat resistance and solvent resistance may decrease, so the above-mentioned range is preferable.

[0127] In addition, examples of suitable polycarbonate diols used in the present invention include UH-CARB, UD-CARB, UC-CARB (Ube Industries, Ltd.), PLACCEL CD-PL, PLACCEL CD-H (Daicel Chemical Industries, Ltd.), Kuraray Polyol C Series (Kuraray Co., Ltd.), Duranol Series (Asahi Kasei Chemicals Corporation), etc. These polycarbonate diols can be used alone or in combination of two or more kinds.

[0128] Furthermore, in the present invention, the resin containing a polycaprolactone segment may contain (or be copolymerized with) other segments or monomers in addition to the polycaprolactone segment, for example, a polydimethylsiloxane segment or a polysiloxane segment, or a compound containing an isocyanate compound, which will be described later.

[0129] In the present invention, a compound containing an isocyanate group described below is preferably reacted with a hydroxyl group of a polycarbonate diol to form a urethane (meth)acrylate, which is then used in the laminate. This allows the components constituting the laminate to have the above-mentioned (2) urethane bond and (1) polycarbonate diol segment, and as a result, the toughness of the laminate can be improved, as well as the stretchability and flexibility.

[0130] [Compounds containing urethane bonds or isocyanate groups] In the present invention, the "urethane bond" refers to the bond represented by Chemical Formula 2 above.

[0131] When the components constituting the laminate have this bond, the toughness and elasticity of the entire laminate can be improved.

[0132] The coating composition contains a commercially available urethane-modified resin, which allows the components constituting the laminate to have urethane bonds. In addition, when forming a laminate, a coating composition containing a compound containing an isocyanate group and a compound containing a hydroxyl group as precursors is applied, dried, and cured to generate urethane bonds, which can be incorporated into the laminate.

[0133] In the present invention, it is preferable to introduce a urethane bond into the components constituting the laminate by reacting an isocyanate group with a hydroxyl group to form a urethane bond. By reacting an isocyanate group with a hydroxyl group to form a urethane bond, it is possible to improve the toughness and stretchability of the laminate.

[0134] In addition, in the case of a resin containing the above-mentioned polycaprolactone segment, polycarbonate segment, or polyalkylene glycol segment, or in the case of a resin having a hydroxyl group, it is also possible to form a urethane bond between this resin and a compound containing an isocyanate group as a precursor by heat or the like.

[0135] When a laminate is formed using a compound containing an isocyanate group and a resin containing a polysiloxane segment having a hydroxyl group, or a component containing a polydimethylsiloxane segment having a hydroxyl group, which will be described later, the laminate can have increased surface slipperiness in addition to the toughness and elasticity, and is also more preferable from the viewpoint of solvent resistance.

[0136] In the present invention, the compound containing an isocyanate group refers to a resin containing an isocyanate group, or a monomer or oligomer containing an isocyanate group. Examples of the compound containing an isocyanate group include (poly)isocyanates such as methylene bis-4-cyclohexyl isocyanate, trimethylolpropane adduct of tolylene diisocyanate, trimethylolpropane adduct of hexamethylene diisocyanate, trimethylolpropane adduct of isophorone diisocyanate, isocyanurate of tolylene diisocyanate, isocyanurate of hexamethylene diisocyanate, and biuret of hexamethylene isocyanate, and block compounds of the above isocyanates.

[0137] Among these compounds containing an isocyanate group, aliphatic isocyanates are preferred because they have higher elasticity and flexibility than alicyclic or aromatic isocyanates. The compound containing an isocyanate group is more preferably hexamethylene diisocyanate. As the compound containing an isocyanate group, isocyanates having an isocyanurate ring are particularly preferred in terms of heat resistance, and isocyanurate of hexamethylene diisocyanate is most preferred. Isocyanates having an isocyanurate ring form a laminate having both elasticity and heat resistance.

[0138] [Polysiloxane segment, polydimethylsiloxane segment] In the laminate of the present invention, the components constituting the laminate may have a segment containing at least one segment selected from the group consisting of a polysiloxane segment and a polydimethylsiloxane segment.

[0139] Furthermore, by using a resin containing a segment containing at least one selected from the group consisting of a polysiloxane segment and a polydimethylsiloxane segment, or a coating composition containing a precursor, as one of the coating compositions forming the laminate, the components constituting the laminate can have these.

[0140] The polysiloxane segment and the polydimethylsiloxane segment will be described below.

[0141] The polysiloxane segment will now be described. In the present invention, the polysiloxane segment refers to a segment represented by Chemical Formula 14, which will be described later.

[0142] Here, polysiloxane includes both low molecular weight ones having about 100 siloxane repeating units (so-called oligomers) and high molecular weight ones having more than 100 siloxane repeating units (so-called polymers).

[0143] [ka]

[0144] R1 and R2 are either a hydroxyl group or an alkyl group having 1 to 8 carbon atoms, and the formula has at least one of each; n is an integer of 100 to 300.

[0145] The polysiloxane segment and polydimethylsiloxane segment will be described in detail later, but the components constituting the laminate have these segments, which can improve the heat resistance and weather resistance, and can improve the slipperiness due to the lubricity of the laminate. More preferably, from the viewpoint of lubricity, it is preferable to include a polydimethylsiloxane segment represented by the chemical formula 20 described later.

[0146] In the present invention, a partial hydrolysate of a silane compound containing a hydrolyzable silyl group, an organosilica sol, or a coating composition in which a hydrolyzable silane compound having a radical polymer is added to the organosilica sol can be used as the resin containing a polysiloxane segment.

[0147] Examples of resins containing polysiloxane segments include complete or partial hydrolysates of silane compounds having hydrolyzable silyl groups, such as tetraalkoxysilane, methyltrialkoxysilane, dimethyldialkoxysilane, γ-glycidoxypropyltrialkoxysilane, γ-glycidoxypropylalkyldialkoxysilane, γ-methacryloxypropyltrialkoxysilane, and γ-methacryloxypropylalkyldialkoxysilane; organosilica sol dispersed in an organic solvent; and organosilica sol having a hydrolyzed silane compound having a hydrolyzable silyl group added to the surface thereof.

[0148] In the present invention, the resin containing a polysiloxane segment may contain (copolymerize) other segments in addition to the polysiloxane segment, for example, a monomer component having a polycaprolactone segment or a polydimethylsiloxane segment.

[0149] When the resin containing polysiloxane segments is a copolymer having hydroxyl groups, a laminate having polysiloxane segments and urethane bonds can be efficiently obtained by forming a laminate using a coating composition containing a resin (copolymer) containing polysiloxane segments having hydroxyl groups and a compound containing an isocyanate group.

[0150] Next, the polydimethylsiloxane segment will be described. In the present invention, the polydimethylsiloxane segment refers to a segment represented by chemical formula 15. Polydimethylsiloxane includes both low molecular weight ones (so-called oligomers) having 10 to 100 dimethylsiloxane repeating units, and high molecular weight ones (so-called polymers) having more than 100 dimethylsiloxane repeating units.

[0151] [ka]

[0152] m is an integer from 10 to 300.

[0153] When the component constituting the laminate has a polydimethylsiloxane segment, the polydimethylsiloxane segment is coordinated to the surface of the laminate. By the polydimethylsiloxane segment being coordinated to the surface of the laminate, the lubricity of the surface of the laminate is improved and the friction resistance can be reduced. This is also preferable from the viewpoint of solvent resistance.

[0154] In the present invention, it is preferable to use, as the resin containing a polydimethylsiloxane segment, a copolymer in which a vinyl monomer is copolymerized with a polydimethylsiloxane segment.

[0155] For the purpose of improving the toughness of the laminate, it is preferable that the resin containing the polydimethylsiloxane segment is copolymerized with a monomer having a hydroxyl group that reacts with an isocyanate group.

[0156] When the resin containing polydimethylsiloxane segments is a copolymer having hydroxyl groups, a laminate having polydimethylsiloxane segments and urethane bonds can be efficiently produced by forming a laminate using a coating composition containing a resin (copolymer) containing polydimethylsiloxane segments having hydroxyl groups and a compound containing an isocyanate group.

[0157] When the resin containing the polydimethylsiloxane segment is a copolymer with a vinyl monomer, it may be any of a block copolymer, a graft copolymer, and a random copolymer. When the resin containing the polydimethylsiloxane segment is a copolymer with a vinyl monomer, it is called a polydimethylsiloxane-based copolymer. The polydimethylsiloxane-based copolymer can be produced by a living polymerization method, a polymer initiator method, a polymer chain transfer method, etc., but it is preferable to use the polymer initiator method and the polymer chain transfer method in consideration of productivity.

[0158] When using the polymer initiator method, copolymerization with other vinyl monomers can be performed using a polymer azo-based radical polymerization initiator represented by Chemical Formula 16. In addition, a two-step polymerization can be performed in which a peroxy monomer and a polydimethylsiloxane having an unsaturated group are copolymerized at low temperature to synthesize a prepolymer having a peroxide group introduced into the side chain, and the prepolymer is then copolymerized with a vinyl monomer.

[0159] [ka]

[0160] m is an integer from 10 to 300, and n is an integer from 1 to 50.

[0161] When using the polymer chain transfer method, for example, HS-CH2COOH, HS-CH2CH2COOH, or the like is added to the silicone oil shown in Chemical Formula 17 to form a compound having an SH group, and then the silicone compound is copolymerized with a vinyl monomer by utilizing the chain transfer of the SH group to synthesize a block copolymer.

[0162] [ka]

[0163] m is an integer from 10 to 300.

[0164] To synthesize a polydimethylsiloxane-based graft copolymer, for example, a compound shown in Chemical Formula 18, i.e., a methacrylic ester of polydimethylsiloxane, can be copolymerized with a vinyl monomer to easily obtain the graft copolymer.

[0165] [ka]

[0166] m is an integer from 10 to 300.

[0167] Examples of vinyl monomers used in copolymers with polydimethylsiloxane include methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, octyl acrylate, cyclohexyl acrylate, tetrahydrofurfuryl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, 2-ethylhexyl methacrylate, stearyl methacrylate, lauryl methacrylate, methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, styrene, α-methylstyrene, acrylonitrile, methacrylonitrile, vinyl acetate, vinyl chloride, and chlorides. Examples of the vinylidene fluoride include vinylidene fluoride, glycidyl acrylate, glycidyl methacrylate, allyl glycidyl ether, acrylic acid, methacrylic acid, itaconic acid, crotonic acid, maleic acid, maleic anhydride, acrylamide, methacrylamide, N-methylol acrylamide, N,N-dimethyl acrylamide, N,N-dimethyl aminoethyl methacrylate, N,N-diethyl aminoethyl methacrylate, diacetone acrylamide, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, and allyl alcohol.

[0168] In addition, the polydimethylsiloxane copolymer is preferably produced by a solution polymerization method in a single or mixed solvent, such as an aromatic hydrocarbon solvent such as toluene or xylene, a ketone solvent such as methyl ethyl ketone or methyl isobutyl ketone, an ester solvent such as ethyl acetate or butyl acetate, or an alcohol solvent such as ethanol or isopropyl alcohol.

[0169] If necessary, a polymerization initiator such as benzoyl peroxide, azobisisobutylnitrile, etc. is used in combination. The polymerization reaction is preferably carried out at 50 to 150° C. for 3 to 12 hours.

[0170] In terms of the lubricity and solvent resistance of the laminate, the amount of the polydimethylsiloxane segment in the polydimethylsiloxane copolymer of the present invention is preferably 1 to 30 mass % relative to 100 mass % of the total components of the polydimethylsiloxane copolymer, and the weight average molecular weight of the polydimethylsiloxane segment is preferably 1,000 to 30,000.

[0171] In the present invention, when a resin containing a polydimethylsiloxane segment is used as the coating composition used to form a laminate, other segments may be contained (copolymerized) in addition to the polydimethylsiloxane segment. For example, a polycaprolactone segment or a polysiloxane segment may be contained (copolymerized).

[0172] The coating composition used to form the laminate may be a copolymer of a polycaprolactone segment and a polydimethylsiloxane segment, a copolymer of a polycaprolactone segment and a polysiloxane segment, a copolymer of a polycaprolactone segment, a polydimethylsiloxane segment and a polysiloxane segment, etc. A laminate obtained by using such a coating composition can have a polycaprolactone segment and a polydimethylsiloxane segment and / or a polysiloxane segment.

[0173] In the coating composition used to form a laminate having polycaprolactone segments, polysiloxane segments, and polydimethylsiloxane segments, the reaction of the polydimethylsiloxane-based copolymer, polycaprolactone, and polysiloxane can be carried out by copolymerization by appropriately adding polycaprolactone segments and polysiloxane segments during the synthesis of the polydimethylsiloxane-based copolymer.

[0174] [Paint composition B] In the laminate of the present invention, it is preferable to form a surface layer by using the following coating composition B and applying it onto a release film or a resin layer.

[0175] Coating composition B is a liquid containing components suitable for constituting the surface layer of the present invention, and contains a resin or precursor suitable for forming the surface layer.

[0176] Coating composition B is not particularly limited, but is preferably a thermosetting resin or an ultraviolet-curing resin, and may be either a thermosetting resin or an ultraviolet-curing resin, or may be a blend of two or more types.

[0177] The thermosetting resin in the present invention preferably contains a resin containing a hydroxyl group and a polyisocyanate compound, and examples of the resin containing a hydroxyl group include acrylic polyol, polyether polyol, polyester polyol, polyolefin polyol, polycarbonate polyol, urethane polyol, etc., which may be used alone or in a blend of two or more kinds. These acrylic polyols, polyether polyols, polyester polyols, polyolefin polyols, polycarbonate polyols, urethane polyols, etc. preferably contain a hydroxyl group.

[0178] The hydroxyl value of the hydroxyl-containing resin is preferably in the range of 1 to 200 mgKOH / g from the viewpoints of durability, hydrolysis resistance, and adhesion when formed into a coating film. If the hydroxyl value is less than 1, the curing of the coating film hardly progresses, and durability and strength may decrease. On the other hand, if the hydroxyl value is more than 200, the curing shrinkage is too large, and adhesion may decrease.

[0179] The acrylic polyol in the present invention is obtained by, for example, polymerizing an acrylic acid ester or a methacrylic acid ester as a component. Such an acrylic resin can be easily produced, for example, by copolymerizing a carboxyl acid group-containing monomer such as (meth)acrylic acid, itaconic acid, or maleic anhydride with a (meth)acrylic acid ester as a component, as necessary. Examples of (meth)acrylic acid esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, methylhexyl (meth)acrylate, cyclododecyl (meth)acrylate, and isobornyl (meth)acrylate. Examples of such acrylic polyols include those manufactured by DIC Corporation (product name "ACRYDIC" (registered trademark) series, etc.), Taisei Fine Chemical Co., Ltd. (product name "ACRYTT" (registered trademark) series, etc.), Nippon Shokubai Co., Ltd. (product name "Acryset" (registered trademark) series, etc.), and Mitsui Chemicals, Inc. (product name "Takelac" (registered trademark) UA series), and these products can be used.

[0180] The polyether polyol in the present invention includes polyethylene glycol or triol, polypropylene glycol or triol, polybutylene glycol or triol, polytetramethylene glycol or triol, and further, addition polymers and block copolymers of these oxyalkylene compounds having different carbon numbers. Examples of such polyether polyols include Asahi Glass Co., Ltd. (trade name "Exenol" (registered trademark) series, etc.) and Mitsui Chemicals, Inc. (trade name "Actocoal" (registered trademark) series, etc.), and these products can be used.

[0181] Examples of the polyester polyol in the present invention include aliphatic polyester polyols obtained by reacting an aliphatic glycol such as ethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, heptanediol, decanediol, or cyclohexanedimethanol with an aliphatic dibasic acid such as succinic acid, adipic acid, sebacic acid, fumaric acid, suberic acid, azelaic acid, 1,10-decamethylenedicarboxylic acid, or cyclohexanedicarboxylic acid as an essential raw material component; and aromatic polyester polyols obtained by reacting an aliphatic glycol such as ethylene glycol, propylene glycol, or butanediol with an aromatic dibasic acid such as terephthalic acid, isophthalic acid, or naphthalenedicarboxylic acid as an essential raw material component.

[0182] Examples of such polyester polyols include those manufactured by DIC Corporation (product name "Polylite" (registered trademark) series, etc.), Kuraray Co., Ltd. (product name "Kuraray Polyol" (registered trademark) series, etc.), and Takeda Pharmaceutical Co., Ltd. (product name "Takelac" (registered trademark) U series), and these products can be used.

[0183] The polyolefin polyol in the present invention is a compound containing a hydroxyl group, among polymers and copolymers of diolefins having 4 to 12 carbon atoms, such as butadiene and isoprene, and copolymers of diolefins having 4 to 12 carbon atoms and α-olefins having 2 to 22 carbon atoms. There is no particular limitation on the method for introducing a hydroxyl group, but for example, there is a method of reacting a diene monomer with hydrogen peroxide. Furthermore, the remaining double bonds may be hydrogen-bonded to make them saturated aliphatic. Examples of such polyolefin polyols include Nippon Soda Co., Ltd. (trade name "NISSO-PB" (registered trademark) G series, etc.) and Idemitsu Kosan Co., Ltd. (trade name "Poly bd" (registered trademark) series, "Epole" (registered trademark) series, etc.), and these products can be used.

[0184] As the polycarbonate polyol in the present invention, for example, a polycarbonate polyol obtained by using only a dialkyl carbonate and 1,6-hexanediol can be used. However, it is preferable to use a polycarbonate polyol obtained by copolymerizing 1,6-hexanediol with 1,4-butanediol, 1,5-pentanediol or 1,4-cyclohexanedimethanol as the diol, since it has lower crystallinity.

[0185] Examples of such polycarbonate polyols include copolymer polycarbonate polyols manufactured by Asahi Kasei Chemicals Corporation (product names "T5650J", "T5652", "T4671", "T4672", etc.) and Ube Industries, Ltd. (product name "ETERNACLL" (registered trademark) UM series, etc.), and these products can be used.

[0186] The urethane polyol containing a hydroxyl group in the present invention is obtained, for example, by reacting a polyisocyanate compound with a compound containing at least two hydroxyl groups in one molecule in such a ratio that the hydroxyl groups are in excess relative to the isocyanate groups. Examples of the polyisocyanate compound used in this case include hexamethylene diisocyanate, toluene diisocyanate, m-xylene diisocyanate, isophorone diisocyanate, etc. In addition, examples of the compound containing at least two hydroxyl groups in one molecule include polyhydric alcohols, polyester diols, polyethylene glycols, polypropylene glycols, polycarbonate diols, etc.

[0187] The polyisocyanate compound used in the thermosetting resin of the present invention refers to a resin containing an isocyanate group, or a monomer or oligomer containing an isocyanate group. Examples of the compound containing an isocyanate group include (poly)isocyanates such as methylene bis-4-cyclohexyl isocyanate, trimethylolpropane adduct of tolylene diisocyanate, trimethylolpropane adduct of hexamethylene diisocyanate, trimethylolpropane adduct of isophorone diisocyanate, isocyanurate of tolylene diisocyanate, isocyanurate of hexamethylene diisocyanate, and biuret of hexamethylene isocyanate, as well as block compounds of the above isocyanates. Examples of polyisocyanate compounds used in such thermosetting resins include those manufactured by Mitsui Chemicals, Inc. (product name "Takenate" (registered trademark) series, etc.), Nippon Polyurethane Industry Co., Ltd. (product name "Coronate" (registered trademark) series, etc.), Asahi Kasei Chemicals Corporation (product name "Duranate" (registered trademark) series, etc.), and DIC Corporation (product name "Burnoc" (registered trademark) series, etc.), and these products can be used.

[0188] The ultraviolet-curable resin in the present invention is not particularly limited, but is preferably a polyfunctional acrylate monomer, oligomer, alkoxysilane, alkoxysilane hydrolysate, alkoxysilane oligomer, urethane acrylate oligomer, or the like, and more preferably a polyfunctional acrylate monomer, oligomer, or urethane acrylate oligomer.

[0189] Examples of polyfunctional acrylate monomers include polyfunctional acrylates having two or more (meth)acryloyloxy groups in one molecule and modified polymers thereof, and specific examples thereof include pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol triacrylate hexanemethylene diisocyanate urethane polymer, etc. These monomers can be used alone or in combination of two or more.

[0190] In addition, commercially available polyfunctional acrylic compositions include Mitsubishi Rayon Co., Ltd. (trade name "Diabeam" (registered trademark) series, etc.), Nippon Synthetic Chemical Industry Co., Ltd. (trade name "SHIKOH" (registered trademark) series, etc.), Nagase & Co., Ltd. (trade name "Denacol" (registered trademark) series, etc.), Shin-Nakamura Chemical Co., Ltd. (trade name "NK Ester" series, etc.), DIC Corporation (trade name "UNIDIC" (registered trademark), etc.), Toagosei Co., Ltd. ("Aronix" (registered trademark) series, etc.), NOF Corporation ("Blenmar" (registered trademark) series, etc.), Nippon Kayaku Co., Ltd. (trade name "KAYARAD" (registered trademark) series, etc.), Kyoeisha Chemical Co., Ltd. (trade name "Light Ester" series, etc.), and these products can be used.

[0191] In order to impart the above-mentioned properties, an acrylic polymer may be used. The acrylic polymer does not contain an unsaturated group, and more preferably has a weight average molecular weight of 5,000 to 200,000 and a glass transition temperature of 20°C or more and 200°C or less. If the glass transition temperature of the acrylic polymer is less than 20°C, the hardness may decrease, and if it exceeds 200°C, the elongation may be insufficient. The more preferred range of the glass transition temperature is 50°C or more and 150°C or less.

[0192] In addition, the acrylic polymer can have a hydrophilic functional group, which can impart hardness to the polymer. Specifically, the hydrophilic functional group can be introduced into the acrylic polymer by copolymerizing an unsaturated monomer having a hydrophilic functional group, such as (meth)acrylic acid, itaconic acid, fumaric acid, or leic acid having a carboxyl group, or an unsaturated monomer having a hydroxyl group, such as 2-hydroxyethyl (meth)acrylate or hydroxypropyl (meth)acrylate, with the unsaturated monomer.

[0193] The weight average molecular weight of the acrylic polymer is preferably 5,000 to 200,000. If the weight average molecular weight is less than 5,000, the hardness may be insufficient, and if the weight average molecular weight is more than 200,000, the moldability including coatability and toughness may be insufficient. The weight average molecular weight can be adjusted by the blending amount of the polymerization catalyst and the chain transfer agent and the type of the solvent used.

[0194] The acrylic polymer content is preferably 1% by mass or more and 50% by mass or less, more preferably 5% by mass or more and 30% by mass or less, based on the total solid content of the coating composition B. By making it 1% by mass or more, the elongation is significantly improved, and by making it 50% by mass or less, the hardness can be maintained, which is preferable.

[0195] [solvent] The coating composition may contain a solvent. The number of types of solvents is preferably from 1 to 20, more preferably from 1 to 10, even more preferably from 1 to 6, and particularly preferably from 1 to 4.

[0196] The term "solvent" as used herein refers to a substance that is liquid at room temperature and pressure and can be evaporated almost entirely in the drying process after application.

[0197] Here, the type of solvent is determined by the molecular structure that constitutes the solvent. In other words, solvents that have the same elemental composition and the same type and number of functional groups but different bond relationships (structural isomers), and solvents that are not structural isomers but do not overlap exactly in any conformation in three-dimensional space (stereoisomers) are treated as different types of solvents. For example, 2-propanol and n-propanol are treated as different solvents.

[0198] Furthermore, when a solvent is contained, it is preferable that the solvent exhibits the following characteristics.

[0199] Condition 1: When solvent B is the solvent with the lowest relative evaporation rate (ASTM D3539-87(2004)) based on n-butyl acetate, the relative evaporation rate of solvent B is 0.4 or less.

[0200] Here, the relative evaporation rate based on the solvent n-butyl acetate is the evaporation rate measured in accordance with ASTM D3539-87 (2004). Specifically, it is a value defined as the relative value of the evaporation rate based on the time required for 90% by mass of n-butyl acetate to evaporate in dry air.

[0201] When the relative evaporation rate of the solvent is greater than 0.4, the time required for the orientation of the polysiloxane segment and / or polydimethylsiloxane segment and the fluorine compound segment to the outermost surface of the laminate is shortened, which may result in a decrease in the solvent resistance of the resulting laminate. In addition, the lower limit of the relative evaporation rate of the solvent is not a problem as long as the solvent can be evaporated and removed from the coating film in the drying process, and in a general coating process, it is sufficient if it is 0.005 or more.

[0202] Solvents include isobutyl ketone (relative evaporation rate: 0.2), isophorone (relative evaporation rate: 0.026), diethylene glycol monobutyl ether (relative evaporation rate: 0.004), diacetone alcohol (relative evaporation rate: 0.15), oleyl alcohol (relative evaporation rate: 0.003), ethylene glycol monoethyl ether acetate (relative evaporation rate: 0.2), nonylphenoxyethanol (relative evaporation rate: 0.25), propylene glycol monoethyl ether (relative evaporation rate: 0.1), and cyclohexanone (relative evaporation rate: 0.32).

[0203] [Other components in the coating composition] The coating composition preferably contains a polymerization initiator, a curing agent, and a catalyst. The polymerization initiator and the catalyst are used to promote curing of the laminate. The polymerization initiator is preferably one that can initiate or promote polymerization, condensation, or crosslinking reaction of the components contained in the coating composition by anionic, cationic, or radical polymerization reaction.

[0204] Various polymerization initiators, curing agents, and catalysts can be used. The polymerization initiators, curing agents, and catalysts may be used alone, or multiple polymerization initiators, curing agents, and catalysts may be used simultaneously. Furthermore, an acid catalyst or a thermal polymerization initiator may be used in combination. Examples of acid catalysts include hydrochloric acid aqueous solution, formic acid, and acetic acid. Examples of thermal polymerization initiators include peroxides and azo compounds. Examples of photopolymerization initiators include alkylphenone compounds, sulfur-containing compounds, acylphosphine oxide compounds, and amine compounds. Examples of crosslinking catalysts that promote the reaction of forming urethane bonds include dibutyltin dilaurate and dibutyltin diethylhexoate.

[0205] The coating composition may also contain other crosslinking agents, such as melamine crosslinkers, such as alkoxymethylol melamines, anhydride crosslinkers, such as 3-methyl-hexahydrophthalic anhydride, and amine crosslinkers, such as diethylaminopropylamine.

[0206] As the photopolymerization initiator, an alkylphenone compound is preferable from the viewpoint of curability. Specific examples of the alkylphenone compound include 1-hydroxy-cyclohexyl-phenyl-ketone, 2,2-dimethoxy-1,2-diphenylethane-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-phenyl)-1-butane, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-(4-phenyl)-1-butane, 2-benzyl-2-dimethylamino-1-(4- morpholinophenyl)-1-butane, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butane, 1-cyclohexyl-phenyl ketone, 2-methyl-1-phenylpropan-1-one, 1-[4-(2-ethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, bis(2-phenyl-2-oxoacetate)oxybisethylene, and polymerized versions of these materials.

[0207] In addition, a leveling agent, an ultraviolet absorber, a lubricant, an antistatic agent, etc. may be added to the coating composition as long as the effect of the present invention is not hindered. As a result, the laminate can contain a leveling agent, an ultraviolet absorber, a lubricant, an antistatic agent, etc. Examples of the leveling agent include acrylic copolymers, silicone-based, and fluorine-based leveling agents. Specific examples of the ultraviolet absorber include benzophenone-based, benzotriazole-based, oxalic acid anilide-based, triazine-based, and hindered amine-based ultraviolet absorbers. Examples of the antistatic agent include metal salts such as lithium salts, sodium salts, potassium salts, rubidium salts, cesium salts, magnesium salts, and calcium salts.

[0208] [Method of manufacturing laminate] The method for producing the laminate of the present invention is not particularly limited, but it is preferable to produce the laminate by a method for producing a laminate having the above-mentioned characteristics, which method includes a step of peeling off the release film from the laminate of the present invention.

[0209] As a method for producing the laminate of the present invention, a method including a step of peeling off the release film from the laminate of the present invention is adopted, whereby the surface of the laminate can be protected from external loads until the laminate is peeled off from the release film.

[0210] When forming the laminate of the present invention on a release film, although there are no particular limitations, it is preferable to manufacture the laminate by a manufacturing method that includes a step of applying a coating composition containing components that constitute a resin layer to the surface of the release film and a step of curing the components, a step of applying a coating composition containing components that constitute a surface layer and a step of curing the components, and further includes a step of peeling off the release film. Alternatively, it is preferable to manufacture the film by a manufacturing method including a step of applying a coating composition containing components constituting the surface layer onto the surface of a release film and a step of curing the components, and further a step of applying a coating composition containing components constituting the resin layer onto the surface layer and a step of curing the components, and further a step of peeling off the release film.

[0211] The order of the above-mentioned resin layer forming step and surface layer forming step may be either one of a method of forming a resin layer first and then forming a surface layer thereon, and a method of forming a surface layer first and then forming a resin layer thereon. From the viewpoint of adhesion between the resin layer and the surface layer, haze suppression of the laminate, and quality improvement, it is more preferable to form a surface layer on the release film surface first and then form a resin layer thereon. In addition, a manufacturing method in which a surface layer is formed on the release film surface first and then a resin layer is formed thereon is preferable because when performing post-processing on the surface layer, the surface layer can be exposed by peeling off the release film at any timing. Hereinafter, the process of applying each coating composition will be referred to as the coating process, the process of drying each coating composition as the drying process, and the process of curing each coating composition as the curing process. Two or more coating compositions may be applied sequentially or simultaneously to form a laminate consisting of two or more layers.

[0212] Here, "sequential application" means that one type of coating composition is applied on a release film, dried, and cured, and then another coating composition is applied thereon, dried, and cured to form a laminate consisting of two or more layers. By appropriately selecting the type of coating composition used, the flexibility and the magnitude of stretchability of the laminate can be controlled. Furthermore, by appropriately selecting the type, composition, drying conditions, and curing conditions of the coating composition, the distribution form of flexibility and stretchability in the laminate can be controlled stepwise or continuously.

[0213] Moreover, "coating simultaneously" means that in the coating step, two or more types of coating compositions are simultaneously coated onto a release film, and then dried and cured.

[0214] In the coating step, the method for coating the coating composition is not particularly limited, but it is preferable to coat the coating composition on the supporting substrate by a dip coating method, a roller coating method, a wire bar coating method, a gravure coating method, a die coating method (U.S. Pat. No. 2,681,294), etc. Furthermore, among these coating methods, the gravure coating method or the die coating method is more preferable as the coating method.

[0215] When two or more types of coating compositions are applied simultaneously, methods such as multi-layer slide die coating, multi-layer slot die coating, and wet-on-wet coating can be used, although there are no particular limitations.

[0216] An example of multi-layer slide die coating is shown in Figure 4. In multi-layer slide die coating, liquid films consisting of two or more types of coating compositions are laminated in order using a multi-layer slide die 31, and then coated onto a supporting substrate or a release film.

[0217] An example of multi-layer slot die coating is shown in Figure 5. In multi-layer slot die coating, liquid films consisting of two or more types of coating compositions are coated and simultaneously laminated onto a supporting substrate or a release film using a multi-layer slot die 32.

[0218] An example of wet-on-wet coating is shown in Figure 6. In wet-on-wet coating, one layer of liquid film made of a coating composition discharged from a single-layer slot die 33 is formed on a supporting substrate, and then, while the liquid film is still wet, a liquid film made of another coating composition discharged from another single-layer slot die 8 is laminated on the liquid film.

[0219] Following the coating step, the liquid film coated on the release film is dried in a drying step. From the viewpoint of completely removing the solvent from the resulting laminate, the drying step preferably involves heating the liquid film.

[0220] Heating methods in the drying process include heat transfer drying (contact with a hot object), convection heat transfer (hot air), radiation heat transfer (infrared rays), and others (microwaves, induction heating), etc. Among these, methods using convection heat transfer or radiation heat transfer are preferred because of the need to precisely uniform the drying speed in the width direction.

[0221] As long as a desired drying rate is obtained, there is no particular limitation, but in order to obtain the above drying rate, the temperature is preferably from 15°C to 129°C, more preferably from 50°C to 129°C, and particularly preferably from 50°C to 99°C.

[0222] The drying step is preferably followed by a further curing operation (curing step) by irradiation with heat or active energy rays.

[0223] As the active energy ray, from the viewpoint of versatility, an electron beam (EB ray) and / or an ultraviolet ray (UV ray) are preferable. When curing with ultraviolet ray, it is preferable that the oxygen concentration is as low as possible in order to prevent oxygen inhibition, and it is more preferable to cure in a nitrogen atmosphere (nitrogen purging). When the oxygen concentration is high, the curing of the outermost surface is inhibited, the curing of the surface is weakened, and the toughness may be reduced. In addition, examples of the type of ultraviolet lamp used for irradiating ultraviolet ray include a discharge lamp type, a flash type, a laser type, and an electrodeless lamp type. When a high-pressure mercury lamp, which is a discharge lamp type, is used, the illuminance of the ultraviolet ray is preferably 100 to 3,000 mW / cm. 2 , more preferably 200 to 2,000 mW / cm 2 , and more preferably 300 to 1,500 mW / cm 2 The ultraviolet irradiation is preferably performed under the conditions described above. The integrated light amount of the ultraviolet light is preferably 100 to 3,000 mJ / cm 2 , more preferably 200 to 2,000 mJ / cm 2 , and more preferably 300 to 1,500 mJ / cm 2 It is best to irradiate ultraviolet light under the following conditions: Here, ultraviolet light illuminance refers to the irradiation strength received per unit area, and varies with lamp output, emission spectral efficiency, diameter of the light-emitting bulb, design of the reflector, and the distance between the irradiated object and the light source. However, illuminance does not vary with transport speed. Also, the integrated amount of ultraviolet light refers to the irradiation energy received per unit area, and is the total amount of photons that reach the surface. The integrated amount of light is inversely proportional to the irradiation speed passing under the light source, and proportional to the number of irradiations and the number of lamps.

[0224] [Application example] The laminate of the present invention has advantages such as excellent optical properties, flexibility, stretchability, tack prevention, transportability, reworkability (repeated bonding and peeling), and conformability, and can be suitably used in applications where these properties are required.

[0225] To name a few examples, it can be suitably used for the surface materials, internal materials, constituent materials, and manufacturing process materials of plastic molded products such as glasses / sunglasses, cosmetic cases, and food containers, aquariums, showcases for exhibitions, smartphone housings, touch panels, color filters, flat panel displays, flexible displays, flexible devices, wearable devices, sensors, circuit materials, electrical and electronic applications, home appliances such as keyboards, remote controls for televisions and air conditioners, mirrors, window glass, buildings, dashboards, car navigation touch panels, vehicle parts such as rearview mirrors and windows, and various printed matter, medical films, films for sanitary materials, medical films, agricultural films, and building materials. EXAMPLES

[0226] Next, the present invention will be described based on examples, but the present invention is not necessarily limited to these.

[0227] [Urethane (meth)acrylate] [Synthesis of urethane (meth)acrylate 1] 100 parts by mass of toluene, 50 parts by mass of methyl-2,6-diisocyanate hexanoate (LDI manufactured by Kyowa Hakko Kirin Co., Ltd.) and 119 parts by mass of polycarbonate diol ("Placcel" (registered trademark) CD-210HL manufactured by Daicel Chemical Industries, Ltd.) were mixed, and the temperature was raised to 40°C and maintained for 8 hours. Then, 28 parts by mass of 2-hydroxyethyl acrylate (Light Ester HOA manufactured by Kyoeisha Chemical Co., Ltd.), 5 parts by mass of dipentaerythritol hexaacrylate (M-400 manufactured by Toagosei Co., Ltd.), and 0.02 parts by mass of hydroquinone monomethyl ether were added and maintained at 70°C for 30 minutes, and then 0.02 parts by mass of dibutyltin laurate was added and maintained at 80°C for 6 hours. Finally, 97 parts by mass of toluene were added to obtain a toluene solution of urethane (meth)acrylate 1 with a solid content concentration of 50% by mass. The number average molecular weight of urethane (meth)acrylate 1 was 5,800.

[0228] [Urethane (meth)acrylate 2] As the urethane (meth)acrylate 2, SUA-017 (manufactured by Asia Industries Co., Ltd., solid content concentration 100% by mass) having a number average molecular weight of 4,600 was used.

[0229] [Photoradical polymerization initiator] [Photoradical polymerization initiator 1] As the photoradical polymerization initiator 1, "Irgacure" (registered trademark) 184 (manufactured by BASF Japan Ltd., solid content concentration 100% by mass) was used.

[0230] [Acrylic polyol] [Acrylic polyol 1] As the acrylic polyol 1, an acrylic polyol containing a hydroxyl group ("Takelac" (registered trademark) UA-702, manufactured by Mitsui Chemicals, Inc., solid content concentration 50 mass %, hydroxyl value: 50 mgKOH / g) was used.

[0231] [Acrylic polyol 2] As the acrylic polyol 2, an acrylic polyol containing a hydroxyl group ("ACRYDIC" (registered trademark) A-823, manufactured by DIC Corporation, solid content concentration 50% by mass, hydroxyl value 30 mgKOH / g) was used.

[0232] [Isocyanate compounds] [Isocyanate compound 1] As the isocyanate compound 1, tolylenediisocyanate ("Coronate" (registered trademark) L, Nippon Polyurethane Industry Co., Ltd., solid content concentration 75% by mass, NCO content 13.5% by mass) was used.

[0233] [Acrylic polymer] Synthesis of acrylic polymer 1 24 parts by mass of dilauroyl peroxide ("Perloyl" (registered trademark) L, manufactured by NOF Corporation) was added to 495 parts by mass of methyl ethyl ketone and heated at 70 ° C for 30 minutes to dissolve, and a solution of 50 parts by mass of methacrylic acid, 90 parts by mass of butyl acrylate, 100 parts by mass of methyl methacrylate and 2.4 parts by mass of 4-methyl-2,4-diphenylpentene-1 ("Nofumar" (registered trademark) MSD, manufactured by NOF Corporation) was added dropwise over 4 hours to polymerize with stirring. After that, stirring was continued for another 2 hours at 80 ° C to obtain a methyl ethyl ketone solution (weight average molecular weight 6,000) of acrylic polymer 1 containing hydrophilic functional groups and having a solid content concentration of 35% by mass.

[0234] [Release film] [Release film 1] As the release film 1, "Cerapeel" (registered trademark) SY (thickness 38 μm, manufactured by Toray Advanced Film Co., Ltd.) was used.

[0235] [Preparation of paint composition A] [Coating composition A1] The following materials were mixed and diluted with methyl ethyl ketone to obtain a coating composition A1 having a solids concentration of 30 mass %.

[0236] Urethane (meth)acrylate solution 1: 100 parts by weight Photoradical polymerization initiator 1: 1.5 parts by mass.

[0237] [Coating composition A2] The following materials were mixed and diluted with methyl ethyl ketone to obtain coating composition A2 having a solids concentration of 30 mass %.

[0238] Urethane (meth)acrylate 2 solution: 50 parts by weight Photoradical polymerization initiator 1: 1.5 parts by mass.

[0239] [Paint composition A3] The following materials were mixed and diluted with methyl ethyl ketone to obtain a coating composition A3 having a solids concentration of 30 mass %.

[0240] Urethane (meth)acrylate solution 1: 50 parts by weight Urethane (meth)acrylate 2 solution: 25 parts by weight Photoradical polymerization initiator 1: 1.5 parts by mass.

[0241] [Preparation of paint composition B] [Coating composition B1] The following materials were mixed and diluted with methyl ethyl ketone to obtain a coating composition B1 having a solids concentration of 20% by mass. Acrylic polyol 1 100 parts by weight Isocyanate compound 1 18.8 parts by mass Acrylic polymer 1 9.6 parts by weight.

[0242] [Paint composition B2] The following materials were mixed and diluted with methyl ethyl ketone to obtain coating composition B2 having a solids concentration of 20% by mass. Acrylic polyol 2 100 parts by weight Isocyanate compound 1 11.8 parts by mass Acrylic polymer 1 8.8 parts by weight.

[0243] [How to make laminates and resin films] A laminate and a resin film were prepared according to the following procedure. The combinations of coating compositions used are shown in Table 1.

[0244] [Method 1] The coating composition was applied onto a release film using a continuous coating device with a slot die coater, with the discharge flow rate from the slot adjusted so that the resin layer after drying had a specified thickness.

[0245] The conditions of the drying air that hits the liquid film from application to drying and hardening are as follows.

[0246] Thereafter, the resin film consisting of the resin layer was peeled off from the release film.

[0247] [Drying process] Air temperature and humidity: Temperature: 80℃, Relative humidity: 1% or less Wind speed: Coating side: 5m / sec, non-coating side: 5m / sec Air flow direction: Coating side: Parallel to the surface of the substrate, Non-coating side: Perpendicular to the surface of the substrate Dwell time: 2 minutes [Curing process] Irradiation power: 400W / cm 2 Accumulated light output: 120mJ / cm 2 Oxygen concentration: 0.1% by volume.

[0248] [Method 2] The coating composition was applied onto a release film using a continuous coating device with a slot die coater, with the discharge flow rate from the slot adjusted so that the surface layer after drying had a specified thickness.

[0249] The conditions of the drying air that hits the liquid film from application to drying and hardening are as follows.

[0250] [Drying process] Air temperature and humidity: Temperature: 80℃ Wind speed: Coating side: 5m / sec, non-coating side: 5m / sec Air flow direction: Coating side: Parallel to the surface of the substrate, Non-coating side: Perpendicular to the surface of the substrate Dwell time: 2 minutes Furthermore, the coating composition was applied onto the surface layer obtained above using the same device, while adjusting the discharge flow rate from the slot so that the thickness of the resin layer after drying would be the specified film thickness.

[0251] The conditions of the drying air that hits the liquid film from application to drying and hardening are as follows.

[0252] Thereafter, the laminate consisting of the surface layer and the resin layer was peeled off from the release film.

[0253] [Drying process] Air temperature and humidity: Temperature: 80℃ Wind speed: Coating side: 5m / sec, non-coating side: 5m / sec Air flow direction: Coating side: Parallel to the surface of the substrate, Non-coating side: Perpendicular to the surface of the substrate Dwell time: 2 minutes [Curing process] Irradiation power: 400W / cm 2 Accumulated light output: 120mJ / cm 2 Oxygen concentration: 200ppm or less.

[0254] [Table 1]

[0255] [Evaluation of laminate, resin layer, and surface layer] The laminate, resin layer, and surface layer were subjected to the following performance evaluations, and the results are shown in Tables 2 and 3. Unless otherwise specified, measurements were performed three times at different locations for one sample in each Example and Comparative Example, and the average value was used.

[0256] [Laminate, Resin Layer Thickness] The thickness of the laminate, resin layer, and surface layer was measured by observing the cross section using a scanning electron microscope (SEM). The thickness of each layer was measured according to the following method. The thickness of each layer was read using software (image processing software ImageJ) from an image of a slice of the cross section of the laminate or resin film taken with an SEM at 3,000 times magnification. The layer thickness was measured at a total of 30 points, and the average value was taken as the measured value.

[0257] [Recovery rate] The laminate or resin film was cut into a rectangle measuring 10 mm wide and 150 mm long to prepare a test piece. The direction of the 150 mm long was aligned with the longitudinal direction of the laminate or resin film. Using a tensile tester (A&D RTG-1210), the initial tensile chuck distance was set to 50 mm, the tensile speed was set to 50 mm / min, and the measurement temperature was set to 23°C. At that time, the sample was stretched to a strain of 10 mm (=20%), and then the tensile load on the sample was released.

[0258] The distance marked as the initial test length before the measurement was measured and defined as L mm, and the elastic recovery rate z% was calculated from the following formula. Recovery rate: z=(1-(L-50) / 1 0) × 100 (%).

[0259] [Storage modulus] Based on the tensile vibration non-resonance method of JIS K7244 (1998) (this is called the dynamic viscoelasticity method), the storage modulus and loss modulus of the resin layer were determined using a dynamic viscoelasticity measuring device "DMS6100" manufactured by Seiko Instruments Inc. In the case of a laminate having a surface layer, the step of producing the surface layer in the above-mentioned production method was omitted, and only the resin layer was produced and used as a test piece. Measurement mode: Tensile Chuck distance: 20mm Test piece width: 10mm Frequency: 1Hz Distortion amplitude: 10μm Initial force amplitude: 40mN Measurement temperature: -100℃ to 100℃ Heating rate: 5℃ / min Loss tangent: (Loss modulus) / (Storage modulus).

[0260] [Hayes] The laminate or resin film was cut into a test piece having a width of 100 mm and a length of 100 mm. Haze was measured using a haze meter (NDH-5000 manufactured by Nippon Denshoku Industries Co., Ltd.) based on JIS K 7136 (2000). The release film was peeled off from the laminate or resin film before the measurement.

[0261] [5% strain stress] The laminate or resin film was cut into a rectangle measuring 10 mm wide and 150 mm long to prepare a test piece. The 150 mm long direction was aligned with the longitudinal direction of the laminate or resin film. Using a tensile tester (A&D RTG-1210), the initial tensile chuck distance was set to 50 mm, the tensile speed was set to 300 mm / min, and the measurement temperature was set to 23°C.

[0262] The load b (N) applied to the sample when the chuck distance was a (mm) was read, and the strain x (%) and stress y (N / mm2) were calculated using the following formula, where k (mm) is the sample thickness before the test. Strain amount: x = ((a-50) / 50) x 100 Stress: y=b / (k×10).

[0263] Of the data obtained above, the stress at a strain of 5% was defined as the 5% strain stress.

[0264] [Evaluation of elasticity 1] The laminate or resin film was pulled by hand and evaluated according to the following criteria. 10 points: Can be transformed with very little force. 7 points: Can be deformed with light pressure. 4 points: Can be deformed with a moderate amount of force. 1 point: Other (requires a strong force to transform, etc.).

[0265] [Evaluation of elasticity 2] The laminate or resin film was subjected to tensile deformation by applying a light force by hand, and the deformation was judged according to the following criteria. 10 points: After deformation, when the load is removed, the material returns to its original shape. 7 points: After deformation, when the load is removed, the material returns to almost its original shape. 4 points: After deformation, when the load is removed, the material regains some of its original shape. 1 point: Other (no restoration at all, etc.).

[0266] [Evaluation of Anti-tack Property and Reworkability] The laminate or resin film was placed on a glass plate and pressed against the glass plate with a load applied in the direction perpendicular to the laminate or resin film. The laminate or resin film was then pulled in its planar direction, and its behavior was evaluated according to the following criteria. For laminates having a surface layer, the surface pressed against the glass plate was the surface having the surface layer. 10 points: The film can be peeled off with almost no resistance and its position can be corrected. 7 points: Can be peeled off with slight force and repositioned. 4 points: Can be peeled off with some force and position can be adjusted. 1 point: Other (can be peeled off but requires a large amount of force, cannot be peeled off, etc.).

[0267] Tables 2 and 3 show the evaluation results of the finally obtained laminates or resin films.

[0268] [Table 2]

[0269] [Table 3] [Explanation of symbols]

[0270] 1 Surface layer 2 Resin layer 3 Surface layer 4 Resin layer 5 Release film 6 Resin layer 7 Surface layer 8 Release film 21 Multi-layer slide die 22 Multi-layer slide die 23 Single layer slot die [Industrial Applicability]

[0271] The laminate of the present invention has advantages such as excellent optical properties, flexibility, stretchability, tack prevention, transportability, reworkability (repeated bonding and peeling), and conformability, and can be suitably used in applications where these properties are required.

[0272] To name a few examples, it can be suitably used for the surface materials, internal materials, constituent materials, and manufacturing process materials of plastic molded products such as glasses / sunglasses, cosmetic cases, and food containers, aquariums, showcases for exhibitions, smartphone housings, touch panels, color filters, flat panel displays, flexible displays, flexible devices, wearable devices, sensors, circuit materials, electrical and electronic applications, home appliances such as keyboards, remote controls for televisions and air conditioners, mirrors, window glass, buildings, dashboards, car navigation touch panels, vehicle parts such as rearview mirrors and windows, and various printed matter, medical films, films for sanitary materials, medical films, agricultural films, and building materials.

Claims

1. A laminate having a surface layer on at least one surface of a resin layer, The storage modulus of the surface layer at 25° C. is 1,000 MPa or more, The haze of the laminate is 10% or less, The recovery rate of the laminate is 50% or more, The following condition 2 is satisfied: the resin layer contains a cured product of urethane (meth)acrylate, The surface layer comprises a (meth)acrylic segment and a urethane segment. Condition 2: The 5% strain stress of the resin layer is 100 MPa or less.

2. The laminate according to claim 1 , which satisfies the following condition 1: Condition 1: The storage modulus of the resin layer at 25° C. is 100 MPa or less.

3. A laminate according to claim 1 or 2, further comprising a supporting substrate, A supporting substrate is in contact with the surface of the surface layer opposite to the resin layer, A laminate comprising a resin layer and a surface layer, the laminate being capable of being peeled off from a supporting substrate.

4. A method for producing the laminate according to claim 1 or 2, comprising the steps of: The method includes a step of applying a coating composition containing components constituting a surface layer to one surface of a supporting substrate, Furthermore, a coating composition containing components constituting a resin layer is applied to the surface of the surface layer opposite to the supporting substrate. A method for producing a laminate, comprising a coating step and a peeling step of removing the supporting substrate from a laminate consisting of a resin layer and a surface layer.

Citation Information

Patent Citations

  • Elastic film and method for producing the elastic film

    JP2008088293A

  • Laminate with thermoplastic polyurethane layer and method for manufacturing thin thermoplastic polyurethane film using the same

    JP2013091223A

  • Foamed urethane sheet, cushioning material and method of manufacturing foamed urethane sheet

    JP2014231170A

  • laminate

    JP2019051692A

  • Stretchable membrane and method for forming same

    JP2019130899A